Acute Cholecystitis in Elderly Patients after Hip Fracture: a Nationwide Cohort Study - Jang, Suk-Yong; Cha, Yong-Han; Mun, Yun-Su; Kim, Sang-Ha; Kim, Ha-Yong; Choy, Won-Sik (Journal of Korean medical science, 2019)
Because acute cholecystitis in elderly hip fracture is not easily distinguishable from other gastrointestinal symptoms and involves atypical clinical behaviors, it may not be diagnosed in the early stage. However, the exact incidences could not be reported. We utilized data from a nationwide claims database and attempted to assess the incidence of acute cholecystitis in elderly hip fracture patients and how cholecystitis affects mortality rates after hip fracture. Study subjects were from the Korean National Health Insurance Service-Senior cohort. From a population of approximately 5.5 million Korean enrollees > 60 years of age in 2002, a total of 588,147 participants were randomly selected using 10% simple random sampling. The subjects included in this study were those who were over 65 years old and underwent surgery for hip fractures. A total of 15,210 patients were enrolled in the cohort as hip fracture patients. There were 7,888 cases (51.9%) of femoral neck fracture and 7,443 (48.9%) cases of hemiarthroplasty. Thirty-six patients developed acute cholecystitis within 30 days after the index date (30-day cumulative incidence, 0.24%). Four of the 36 acute cholecystitis patients (11.1%) died within 30 days versus 2.92% of patients without acute cholecystitis. In the multivariate-adjusted Poisson regression model, hip fracture patients with incident acute cholecystitis were 4.35 (adjusted risk ratio 4.35; 95% confidence interval, 1.66-11.37; = 0.003) times more likely to die within 30 days than those without acute cholecystitis. Incidence of acute cholecystitis in elderly patients after hip fracture within 30 days after the index date was 0.24%. Acute cholecystitis in elderly hip fracture patients dramatically increases the 30-day mortality rate by 4.35-fold. Therefore, early disease detection and management are crucial for patients.